COFFEE TERRITORIALIZATION IN CAPARAÓ CAPIXABA - Tavares, Beatriz Carvalho; Machado, Marcello de Barros Tomé; Valduga, Vander (Mercator, 2023)
Brazil has several regions shaped by the insertion of the coffee economy, an arrangement that highlights the coffee production chain as a structuring element of the territory. This article aims to characterize the territorialization of the coffee production chain in the Caparaó Capixaba region. The qualitative, exploratory, descriptive, and ethnographic research is divided into three stages: bibliographic, fieldwork and interviews. The field research lasted from November 2020 to January 2021. The interviews, conducted online, occurred between September and November 2021. The respondents were 15 coffee producers in the municipalities of Iúna and Irupi, in Caparaó Capixaba, Brazil. Consequently, the formation of Caparaó territoriality from the region's historic coffee culture is evident. Thus, the study increases the understanding of the production, consumption, and commercialization of the region's coffee. Some essential factors considered are the appropriation of space by producers, resignification of practices and territory through work, reinforcement of local identity, formation of the coffee landscape and subsequent productive differentiation through the focus on specialty coffees. Finally, visibility is given to coffee growers' protagonism in a region neglected in recent decades due to low quantitative productivity but which boasts expressive results in agroecological, family and specialty coffee production.  Keywords : Appropriation. Identity. Work. Landscape Coffee Production.